Regional Strategy, Municipality Plans and Site Designs for Energy Transition in Amsterdam, The Netherlands: How Sustainable Are Implementation Processes on Different Spatial Levels? - Picchi, Paolo; Oudes, Dirk; Stremke, Sven (Sustainability, 2023)
Energy transition has a prominent role in 21st-century urban agendas. Worldwide, cities pursue the local implementation of international, national and regional agendas aiming at a sustainable energy transition. Landscape integration, multifunctionality and community participation are three of the key concepts here. These concepts are interpreted differently across the different spatial levels. The object of this paper is to analyse the application of the three sustainability concepts at the regional, local and site levels for the city of Amsterdam, the Netherlands. The results show that the degree of implementation of the concepts depends on what factors are considered important at each spatial level. At the regional and local levels, landscape integration with regards to social factors such as finances and co-ownership drive successful implementation, thanks to the organisation of effective participatory processes. At the site level, landscape integration and multifunctionality with regards to spatial factors such as the ecological, recreational and historical landscape factors drive successful implementation through effective landscape design activities. However, the sustainability of the energy transition implementation process is affected by a lack of social-ecological systems thinking. Participation processes—if present—focus either on social or spatial factors but fail to interconnect them. The regional and local levels that currently demonstrate major abstraction and separation of social and spatial factors would benefit from effective exchange with the site level. At that scale, design activities are the arena to combine and reconcile social and spatial factors.